Genomic characterization of colistin-resistant Klebsiella pneumoniae isolated from intensive care unit patients in Egypt - Eriny T. Attalla; Amal M. Khalil; Azza S. Zakaria; Dave J. Baker; Nelly M. Mohamed (BMC, 2023)
Abstract Background Egypt has witnessed elevated incidence rates of multidrug-resistant Klebsiella pneumoniae infections in intensive care units (ICUs). The treatment of these infections is becoming more challenging whilst colistin-carbapenem-resistant K. pneumoniae is upsurging. Due to the insufficiently available data on the genomic features of colistin-resistant K. pneumoniae in Egypt, it was important to fill in the gap and explore the genomic characteristics, as well as the antimicrobial resistance, the virulence determinants, and the molecular mechanisms of colistin resistance in such a lethal pathogen. Methods Seventeen colistin-resistant clinical K. pneumoniae isolates were collected from ICUs in Alexandria, Egypt in a 6-month period in 2020. Colistin resistance was phenotypically detected by modified rapid polymyxin Nordmann/Poirel and broth microdilution techniques. The isolates susceptibility to 20 antimicrobials was determined using Kirby-Bauer disk diffusion method. Whole genome sequencing and bioinformatic analysis were employed for exploring the virulome, resistome, and the genetic basis of colistin resistance mechanisms. Results Out of the tested K. pneumoniae isolates, 82.35% were extensively drug-resistant and 17.65% were multidrug-resistant. Promising susceptibility levels towards tigecycline (88.24%) and doxycycline (52.94%) were detected. Population structure analysis revealed seven sequence types (ST) and K-types: ST383-K30, ST147-K64, ST17-K25, ST111-K63, ST11-K15, ST14-K2, and ST525-K45. Virulome analysis revealed yersiniabactin, aerobactin, and salmochelin siderophore systems in ˃ 50% of the population. Hypervirulence biomarkers, iucA (52.94%) and rmpA/A2 (5.88%) were detected. Extended-spectrum β-lactamase- and carbapenemase-producers accounted for 94.12% of the population, with bla CTX-M-15, bla NDM-5, and bla OXA-48 reaching 64.71%, 82.35%, and 82.35%, respectively. Chromosomal alterations in mgrB (82.35%) were the most prevailing colistin resistance-associated genetic change followed by deleterious mutations in ArnT (23.53%, L54H and G164S), PmrA (11.76%, G53V and D86E), PmrB (11.76%, T89P and T134P), PmrC (11.76%, S257L), PhoQ (5.88%, L322Q and Q435H), and ArnB (5.88%, G47D) along with the acquisition of mcr-1.1 by a single isolate of ST525. Conclusions In this study, we present the genotypic colistin resistance mechanisms in K. pneumoniae isolated in Egypt. More effective antibiotic stewardship protocols must be implemented by Egyptian health authorities to restrain this hazard and safeguard the future utility of colistin. This is the first characterization of a complete sequence of mcr-1.1-bearing IncHI2/IncHI2A plasmid recovered from K. pneumoniae clinical isolate belonging to the emerging high-risk clone ST525.